ANALISIS ASESMEN PERKEMBANGAN BAHASA PADA ANAK USIA 5-6 TAHUN DI TK PEMBINA 1 MEDAN - Sri Hariyanti Manurung; Muftila Alsiana Putri; Fepriana Asiska; Sondang Kiki Febrianti; Chronika Febrianti; Fely Eclasya; Artha Mahindra Diputra (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Language is an effort of thoughts and feelings to convey meaning to other people which is used as a means of communication. This study aims to determine: (1) the development of language skills of children aged 5-6 years in accordance with the Standards for Child Development Achievement Levels (STPPA) and (2) to determine the development of language skills of group B children in Kindergarten Pembina 1 Medan. This research is a qualitative descriptive study involving 15 children in class B, data were collected through observation, document analysis and analyzed qualitatively using data reduction, data display, drawing conclusions. Then all indicators of achievement of language development can develop according to the level of development. The results of this study indicate an increase in children's language development in TK Pembina 1 Medan. This is proven by an increase in children's language development with an average number of BB 6,6%, MB 20%, BSH 66,6%, and BSB 6,6%. And with this final observation, the research can be said to be successful because the desired data has been obtained by group B children at TK Pembina 1 Medan.